Pengaruh Social Media Marketing, Life Style, dan Store Atmosphere terhadap Keputusan Pembelian Konsumen Mixue di Yogyakarta - Lazuardy, Ilman Taufiq (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This research aims to determine the influence of Social Media Marketing, Life Style, and Store Atmosphere on MiXue Consumer Purchasing Decisions in Yogyakarta. The independent variables in the research consist of Social Media Marketing, Life Style, and Store Atmosphere, as well as Purchase Decisions as the dependent. The population in this study were all students who were taking undergraduate studies in Yogyakarta. The sampling technique uses a non-probability sampling model with a saturated sample method. The number of respondents in this study was 100 people. Data collection was carried out using a questionnaire. The data analysis methods used are instrument tests, basic assumption tests, classical assumption tests, and data analysis consisting of the t test, F test and multiple linear regression analysis. The results of this research show that Social Media Marketing has a positive influence on Purchasing Decisions, Life Style has a positive influence on Purchasing Decisions, and Store Atmosphere has a positive influence on Purchasing Decisions.